Modelled versus observed open cut performance in weak transition rock: the Dubbo Quarry case study - Trani, D.; Hellmuth, J.; Thompson, J. (Slope Stability 2020: Proceedings of the 2020 International Symposium on Slope Stability in Open Pit Mining and Civil Engineering, 2020)
As open pit mining advances, the importance of ensuring the geotechnical slope stability of the cut face becomes critical particularly when transitioning within a weak rock zone. One of the essential components of day-to-day operations is the monitoring of cut geometries which plays a key role in assisting geotechnical engineers and mine operators in maintaining mine safety and production schedules. This paper presents a case study of a basalt quarry site in southwest Dubbo NSW wherein mining of the previously blasted bench of the more competent, fine-grained basalt was restricted due to the likely risk of collapse of the adjacent remaining cut face comprising weak, altered basalt that was believed to have been steeply deposited against a lithic sandstone. Spatial analysis of deformation point measurement data derived from traditional geodetic prism monitoring was performed. A simplified wedge stability analysis via limit equilibrium method was then carried out based on likely combination of shear strength parameters that could reasonably suit the observed gradual geometric changes of the cut face. A review of the reported geometry following the actual collapse of the cut face indicated a broad agreement with the modelling outcome, which in turn revealed that the adopted simplified analytical methodology based on observed deformations, in combination with a good understanding of the geologic setting, can be used to estimate likely performance of cut faces in weak transition rocks.